1975
DOI: 10.1136/pgmj.51.598.510
|View full text |Cite
|
Sign up to set email alerts
|

Renal failure in obstructive jaundice—clinical aspects

Abstract: Summary The patient with obstructive jaundice has an increased risk of developing renal failure. The commonest clinical situations in which this is seen is after surgical operation, as a result of percutaneous cholangiography or in association with severe ascending cholangitis. The risk of acute renal failure is decreased by ensuring adequate hydration and maintaining a high urine flow, if necessary using mannitol or some other osmotic diuretic. In patients undergoing percutaneous cholangiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…The association between obstructive jaundice and acute renal failure (ARF) is well-recognized; ARF may develop in patients with jaundice caused either by operation or septicemia (or both), but is rarely described [ 25 ]. Bismuth et al (1975) reported an association between AC and ARF in a large-scale trial [ 24 ], which included 283 hospitalized patients with confirmed cholangitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between obstructive jaundice and acute renal failure (ARF) is well-recognized; ARF may develop in patients with jaundice caused either by operation or septicemia (or both), but is rarely described [ 25 ]. Bismuth et al (1975) reported an association between AC and ARF in a large-scale trial [ 24 ], which included 283 hospitalized patients with confirmed cholangitis.…”
Section: Discussionmentioning
confidence: 99%
“…AKI according to the guidelines is defined as any of the following: Increase in serum creatinine (SCr) by X0.3 mg/dl within 48 hours; or Increase in SCr to X1.5 times baseline, which is known or presumed to have occurred within the prior 7 days; or Urine volume 0.5 ml/kg/h for 6 hours. Although two very old studies on renal failure associated with AC have appeared [ 24 , 25 ], no study has applied the KDIGO guidelines to evaluate the incidence, risk factors, or clinical outcomes of AKI in association with AC, which was the goal of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive jaundice may be a life-threatening condition due to the interplay of various factors: ascending cholangitis (Boey & Lawrence 1980), acute renal failure (Dawson 1975), hampered defence mechanisms with poor antibiotic penetration (Dawson 1981), high serum fibrinogen/fibrin degradation products (Allison et al 1979), and peripheral and portal endotoxaemia (Bailey 1976). Biliary decompression is therefore important, as well as being necessary to relieve the attendant unpleasant symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that patients with obstructive jaundice, are unable to tolerate even moderate hemorrhage [6,25], There is evidence indicating that the functional reserve of the liver in jaundiced patients or animals depends on the mitochondrial oxidative phosphorylation activity [17], and pronounced derangement of liver mitochondria has been found to occur, with progressive deterioration of the patients' clinical status [16]. It has also been reported that jaundiced animals in which impairment of the liver mitochondria is likely to occur are particularly susceptible to irrevers ible hemorrhagic shock [21], In order to elucidate the possible causes of the impairment of the hepatic energy status in jaundiced animals subjected to hemorrhagic hypo tension, changes in plasma proteins and hematocrit (Ht) are analyzed, and the effects on circulatory disturbances are discussed in comparison with changes in ATP.…”
Section: Introductionmentioning
confidence: 99%